SUATU FLAVONOID DARI TUMBUHAN MILLETTIA ICHTHYOCHTONA - Bialangi, Nurhayati (Sainstek, 2007)
Millettia, one of the main genus of Fabaceae, known to produce flavonoid compounds. Some isoflavones compounds such as jamaicin, were found from the leaves of M. ichthyochtona afforded. Compound Jamaicin was found for the from M. ferruginea. Struktur determination of these compounds was carried out based on physical and spectroscophic method (UV,IR, 1H-NMR, dan 13C-NMR).